Labor market opportunities for women in the digital age - Christiane Krieger-Boden; Alina Sorgner (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
Digitalization offers a variety of opportunities for female empowerment and for a more equal female participation in labor markets, financial markets, and entrepreneurship. Currently, digitalization seems to favor female labor force, since women face on average lower risk of being replaced by machines, as compared to men. Women's often superior social skills represent a comparative advantage in the digital age, and this is particularly so when social skills are complemented with higher education and advanced digital literacy. However, the same barriers and deficits that obstruct women's current advancement in many countries may deprive them from many beneficial opportunities in the digital age, including new entrepreneurial opportunities. Major efforts by policy makers are required to invalidate these barriers. New digital technologies should be used more decisively to achieve the goal of gender equality.
Keywords: O3; J7; 330; Digitalization; gender equality; labor markets; entrepreneurship; financial inclusion